STUDI KEBERHASILAN SISTEM PERENCANAAN STRATEGI PEMASARAN PADA FOOT.LO.GUE - Diana Novita (Jurnal Ilmiah Econosains, 2017)
Marketing strategy in online business has many methods and variaty that some business online should adapt to. Not all those methods are fit for every online business. Every online business must be has their characteristic that showing differences amoung them. With this conditions, we want to give some alternative to make a marketing planning. By making a nice and attractive advertising, can increase the amount of selling products. So that, we have to think smart on making the advertisement. Nowadays, many online shop trying to advertise their products throught facebook, instagram and joining in some marketplace that are so many in Internet. By signing for the paid advertisement, an online shop can put their advertise at the eye catching spot in facebook page, in google, in some spot of marketplace (for exampel like in tokopedia, we can put our store at the top of the list by paying amount of money). Mostly we can find it on facebook as a suggested page, in google as a goole advertisement, in tokopedia as a gold merchant, premium accounts in instagram and etc.. In this field, the online shop can put their advertisement with attractive picture and attractive words to make people click the link and directly go to their store. Keywords : online orders, online marketing, success study, online, business, e-commerce